Scientific researches in atomic force microscopy - Wright, Kate (NY Research Press, 2015)
This book elucidates the scientific researches in the field of atomic force microscopy. The invention of the atomic force microscope (AFM) brought about drastic changes in the field of surface analysis. It proved to be a critical investigative resource and method, used for qualitative and quantitative study of surfaces with sub-nanometer resolutions. Additionally, samples analyzed through this microscope don't need prior preparation procedures. This prevents any alterations or adverse effects which may damage the sample while allowing a three dimensional study of the exterior surface. This book presents latest work by masters of this method across the globe. This method has found ready acceptance in procuring important information in a diverse spectrum of fields. Since its inception in 1986, it has found multiple uses across manufacturing, research and advancement fields.